Understanding Youth Transition as 'Becoming': Identity, Time and Futurity - Worth, Nancy (Elsevier, 2009)
Drawing on recent work in psychology, philosophy, and youth geographies, this article responds to calls for theoretical rigour in children's geographies by developing the concept of becoming for youth transitions research. Becoming has been used by psychologist Gordon Allport (1955) in his work on the processual nature of personal identity, while Elizabeth Grosz (1999) has used the concept of becoming to explore conceptions of time as a lived experience, focusing on the dynamics of time as duration. This article uses the unifying concept of futurity to tie together the works of Allport and Grosz, exploring how the concept of becoming can be used to consider the inherent complexities of contemporary youth transitions. To demonstrate the value of working with these reconceptualizations, examples of becoming will be explored through research with visually impaired young people. This research productively uses narrative and a life mapping technique to capture the messiness of becoming, seeing transition through the scale of a life and important life events. (C) 2009 Elsevier Ltd. All rights reserved.
The final publication is available at Elsevier via http://dx.doi.org/10.1016/j.geoforum.2009.07.007. © 2009. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/
Keywords: Becoming; Transition; Youth-geographies of Time; Identity